Network cost allocation methods for pay-as-bid peer-to-peer energy trading: A comparison - Noorfatima, N.; Choi, Y.; Onen, A.; Jung, J. (Energy Reports, 2022)
In pay-as-bid peer-to-peer (P2P) energy trading, various types of prosumers and consumers can participate, regardless of their offers. Thus, various types of participants impact the network differently. However, very few pay-as-bid P2P energy trading studies have specifically discussed appropriate compensation for network usage, although the market is implemented in existing utility-owned grids. Therefore, to improve the performance of pay-as-bid P2P energy trading, it is important to determine the appropriate compensation to utilities for network usage. This study aims to obtain an appropriate network cost allocation method for pay-as-bid P2P energy trading. Hence, the authors present a review of pay-as-bid P2P market mechanisms and various network cost allocation (NCA) methods. Additionally, a comprehensive evaluation framework is proposed to determine the most appropriate NCA method for the pay-as-bid P2P energy trading system. A comparison was made between various NCA methods to investigate the outcomes of the implementation of different NCA methods to various market conditions. The study constructs a case study based on the operator-oriented P2P model to represent the pay-as-bid P2P energy trading system. The simulation of pay-as-bid P2P energy trading with large participant number is applied in the IEEE 69-bus distribution system. The study concluded that applying the appropriate NCA method would improve the performance of pay-as-bid P2P energy trading operation.
Keywords: Allocation methods; Energy trading; Evaluation framework; Network cost allocation; Network usage; Network usage cost; Pay as bid; Peer to peer; Peer-to-peer energy trading; Performance; Evaluation framework; Network cost allocation; Network usage cost; Pay-as-bid; Peer-to-peer energy trading